Highly selective capture of minicircle DNA biopharmaceuticals by a novel zinc-histidine peptide conjugate - Gaspar, Vítor Manuel Abreu (2018)
The use of minicircle DNA (mcDNA) biomolecules as a pharmaceutical product holds remarkable potential due to their improved therapeutic efficacy in comparison with standard non-viral gene expression vectors. However, mcDNA translation into clinical application is still highly restricted due to the lack of robust technologies for minicircles detection and purification. In this study, the potential of a zinc-binding histidine-based peptide to function as a novel ligand for mcDNA recovery was investigated by using high-throughput surface plasmon resonance (SPR) analysis. The histidine-based peptide successfully bound zinc cationic ions and had affinity towards mcDNA biomolecules as confirmed by the dynamic binding responses obtained in SPR experiments. Notably, the obtained results indicate that not only zinc-peptide ligands are able to bind mcDNA with very high affinity (KD = 4.21 × 10−10 M), but also that this interaction is mostly dependent on buffer type. In general, the findings indicated that Zn2+ bound peptide has high affinity to mcDNA in low ionic strength buffers, whereas with high salt buffers no binding is detected. Overall, the novel zinc-binding peptide has shown to have suitable properties for mcDNA binding and recovery under experimental conditions that assure genetic material stability. More importantly, the straightforward approach of employing simple biomimetic ligands for mcDNA capture will contribute for development of new technologies to purify DNA biopharmaceuticals.